2013
DOI: 10.1021/ez4000669
|View full text |Cite
|
Sign up to set email alerts
|

Funeral Pyres in South Asia: Brown Carbon Aerosol Emissions and Climate Impacts

Abstract: Atmospheric heating caused by anthropogenically emitted carbonaceous aerosols contributes to one of the largest uncertainties in climate forcing over south Asia (SA). Past studies have identified the combustion of fossil fuels and residential biofuels as being the dominant emitter of light-absorbing black carbon aerosols over this region. Here, we measure emissions from open-air burning of funeral pyres, a deep-rooted and widely prevalent custom in SA, and find that large amounts (≈98% by mass) of light-absorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 42 publications
4
31
2
Order By: Relevance
“…A more recent study by Srinivas and Sarin (2014a) has documented that the MAE of BrC could account for~40e60% relative to that of EC in PM 2.5 samples collected during early winter months (NoveDec) from a downwind sampling site in the IGP. Our results are also consistent with that documented for water-soluble BrC emissions from biofuel burning, which show the relative contribution of MAE of BrC at 300 and 500 nm compared to EC are 70 and 26%, respectively (Chakrabarty et al, 2014).…”
Section: Mass Absorption Efficiency Of Brcsupporting
confidence: 91%
“…A more recent study by Srinivas and Sarin (2014a) has documented that the MAE of BrC could account for~40e60% relative to that of EC in PM 2.5 samples collected during early winter months (NoveDec) from a downwind sampling site in the IGP. Our results are also consistent with that documented for water-soluble BrC emissions from biofuel burning, which show the relative contribution of MAE of BrC at 300 and 500 nm compared to EC are 70 and 26%, respectively (Chakrabarty et al, 2014).…”
Section: Mass Absorption Efficiency Of Brcsupporting
confidence: 91%
“…In this study, the estimated EC mass in aerosol samples has been approximated to be the BC mass [40,41]. This approximation, while having found wide usage in the aerosol community, has its limitations.…”
Section: Analysis Methods and Associated Uncertaintiesmentioning
confidence: 99%
“…This effect is much higher over South Asia. In contrast to BC, the organic carbon (OC) aerosol has been traditionally considered as purely light-scattering particles but studies have shown OC to also absorb light, predominantly at shorter wavelengths [Alexander et al, 2008;Andreae and Gelencser, 2006;Chakrabarty et al, 2014;Kirchstetter and Novakov, 2004;Moosmüller et al, 2011;Sun et al, 2007]. These light-absorbing organic aerosols, termed brown carbon (BrC), may thus, next to BC, also contribute to a positive direct radiative effect on climate (+0.04 to +0.11 W m À2 [e.g., Bahadur et al, 2012;Chung et al, 2012;Feng et al, 2013]).…”
Section: Introductionmentioning
confidence: 99%